ECG-synchronized CT angiography in 324 consecutive pediatric patients: spectrum of indications and trends in radiation dose - Meinel, Felix Gabriel; Henzler, Thomas (Pediatric cardiology, 2014)
The aim of the study is to describe the spectrum of indications for pediatric ECG-synchronized CT angiography (CTA), the main determinants of radiation exposure, and trends in radiation dose over time at a single, tertiary referral center. The study was IRB approved and HIPAA compliant with informed consent waived. Between 2005 and 2013, 324 pediatric patients underwent ECG-synchronized CTA to evaluate known or suspected cardiovascular abnormalities (109 female, median age 8.1 years). The effective dose (ED) was calculated using age-specific correction factors. Univariate and multivariate regression analyses were performed to identify predictors of radiation dose. The most common primary indications for the CTA examinations included known or suspected coronary pathologies (n = 166), complex congenital heart disease (n = 73), and aortic pathologies (n = 41). Median radiation exposure decreased from 12 mSv for patients examined in the years 2005–2007 to 1.2 mSv for patients examined in the years 2011–2013 (p < 0.001). Patients scanned using a tube potential of 80 kV (n = 259) had a significantly lower median radiation dose (1.4 mSv) compared to patients who were scanned at 100 kV (n = 46, median 6.3 mSv) or 120 kV (n = 19, median 19 mSv, p < 0.001). Tube voltage, followed by tube current and the method of ECG-synchronization were the strongest independent predictors of radiation dose. Growing experience with dose-saving techniques and CTA protocols tailored to the pediatric population have led to a tenfold reduction in radiation dose over recent years and now allow routinely performing ECG-synchronized CTA in children with a radiation dose on the order of 1 mSv.